Second-level hospital health professionals' attitudes to lesbian, gay, bisexual and transgender parents seeking health for their children - Chapman, Rose; Watkins, R.; Zappia, T.; Combs, S.; Shields, L. (2012)
Aim. The aim of the study was to assess health professionals' knowledge, attitudes and beliefs regarding lesbian, gay, bisexual and transgender parents accessing health care for their children. Background. Lesbian, gay, bisexual and transgender parents can be reluctant to reveal their sexual orientation to health professionals, and consequently, they may not receive adequate or timely provision of health care. Currently, there is little research in this area. Design. Descriptive, comparative study of 86 health professionals using a cross-sectional survey design with a set of validated, anonymous questionnaires. Method. Associations between variables were assessed using chi-squared tests of independence, and differences between groups were assessed using the Mann-Whitney U-test or the Kruskal-Wallis one-way analysis of variance test. Content analysis was used to examine responses to open-ended questions. Results. Knowledge and attitude scores were significantly associated with race, religious beliefs, frequency of attendance at religious services and having a friend who is openly lesbian, gay, bisexual and transgender. Conclusions. Information gained from this study will assist clinicians and hospital management to develop policies and practices that ensure lesbian, gay, bisexual and transgender families receive equitable, high-quality and holistic health care. Relevance to clinical practice. Properly implemented family-centred care is an ideal model to provide care for lesbian, gay, bisexual and transgender families. However, the benefits of family-centred care can only be realised fully if health professionals delivering that care are sensitive to the context, functions and constructs of all the families they encounter. © 2012 Blackwell Publishing Ltd.